2018
DOI: 10.1007/8904_2018_103
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairments and Subjective Cognitive Complaints in Fabry Disease: A Nationwide Study and Review of the Literature

Abstract: Fabry disease is a rare progressive X-linked lysosomal storage disorder which leads to neuropathic pain, organ dysfunction and cerebral pathology. Few studies have investigated cognitive impairment in Fabry disease and these previous studies are difficult to compare due to heterogeneous methodological designs and small cohorts. The objective was to investigate the frequency of cognitive impairment in the Danish nationwide cohort of Fabry patients. Further, we examined if subjective cognitive complaints were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
33
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 27 publications
5
33
1
Order By: Relevance
“…In the general population, these cerebrovascular disorders cause cognitive deficits such as impaired executive functioning and vascular dementia . Several studies have shown a relation between FD and objective cognitive impairment (OCI) . In addition, we recently established that stroke is independently related to OCI in FD …”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…In the general population, these cerebrovascular disorders cause cognitive deficits such as impaired executive functioning and vascular dementia . Several studies have shown a relation between FD and objective cognitive impairment (OCI) . In addition, we recently established that stroke is independently related to OCI in FD …”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, while subjective cognitive complaints are often mentioned by FD patients, these seem to be related to depressive symptoms rather than OCI . Subjective cognitive complaints therefore probably provide little information on the presence of OCI in FD, complicating the estimation of cognition by clinicians.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…WMLs, stroke and depression in itself are known to result in objective cognitive impairment (OCI) in the general population 4 . Previous studies on OCI in FD were limited by small sample size, often did not incorporate neuroimaging, combined WMLs and stroke as a single entity and did not differentiate between patient groups with different FD phenotypes and sex 3,57 . Small study populations also restricted the identification of variables related to OCI in FD.…”
Section: Introductionmentioning
confidence: 99%